English Register Used in Soccer Column of “Top Skor” Newspaper - Endah Yuniartiah (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2018)
The objectives of mini research done the writer are to describe the linguistic forms of the register used in soccer column of “Top Skor” newspaper and to describe the meaning of register used in soccer column of “Top Skor” newspaper. The writer uses descriptive qualitative in conducting this research. This is due to the fact that the purpose of this research is describing the facts or phenomena systematically and accurately. In this research, the data are taken from ‘Top Skor column. The data of the research are sentences containing the register words and phrases used in soccer column’s language in ‘Top Skor’ newspaper. In collecting the data, the writer uses documentation method. The ways are searching and collecting the newspapers. The writer analyzes the data by classifying the data which can be categories as the register, analyzing the data by identifying the linguistic form of the words and phrases, analyzing the context of situation of the data, identifying the differences between lexical and contextual meaning, drawing conclusion and suggestion based on the data analysis. The writer found 46 data of word (42 nouns, 2 verbs and 2 adjectives). The percentage is around 64% of the total findings (60% noun, 2.7% verb and 2.7% adjective). The writer finds the high frequency data of register meaning are in contextual meaning. The analysis based on the content of word shows that 55 contextual meaning that covers 78.6% of the total findings. There are 15 lexical meaning that covers 21.4% of the total findings.